Use of The Heat Treatment Method as An Alternative to Commercial Kit-Based Nucleic Acid Extraction Method for Detecting SARS-CoV-2 Using RT-qPCR Technique under Reagent Limited Conditions - Alhawaris, Alhawaris; Yadi, Yadi; Tandirogang, Nataniel (Jurnal Kesehatan Pasak Bumi Kalimantan, 2024)
The increase in the number of COVID-19 cases could cause disruptions to the global supply chain of commercial kits for the extraction of SARS-CoV-2 nucleic acid so that the COVID-19 screening process has the potential to be hampered. Another alternative method that can be used is the heat-treatment (HT) method. This study aims to assess the quality of the results of the RT-qPCR examination for the detection of SARS-CoV-2 using the HT nucleic acid extraction method. The samples were nasopharyngeal and oropharyngeal swabs and then underwent nucleic acid extraction using the magnetic beads extraction (MBE) / commercial kit and the HT method on the same day (less than 6 hours). The nucleic acid extraction results from both methods were then amplified using the RT-qPCR technique, then compared and analyzed the results. The results showed that qualitatively there was a very significant difference in the interpretation of the results between the two nucleic acid extraction methods (McNemar test, p = 0; p < 0.01). Qualitative comparative analysis also showed that there were very significant differences in ct (cycle threshold) values in the SARS-CoV-2 genes detected between the two nucleic acid extraction methods (McNemar test, p = 0; p < 0.01). While the value of ct in human gene between the two methods of nucleic acid extraction qualitatively there was no significant difference (McNemar test, p = 1; p > 0.05). The use of HT method for extraction will be more effective on cells or microorganisms that have genetic material in the form of DNA than RNA. The HT method is not recommended for use in the diagnosis of COVID-19. The use of this method as a screening in moderate to severe symptomatic populations under conditions of limited extraction reagents may be considered.Keywords:  SARS-CoV-2, COVID-19, Heat-Treatment Method, Nucleic Acid Extraction, RT-qPCR